Draft Annual Plan 1988-89 (Plan Outline) Vol.-I Government of Manipur - Planning Commission (Planning Commission, 1987)
During the year 1987-88 the State faced a severe flood in day in September, when the rainfall received is 392.2 mm. against the normal rainfall of 135.7 mm. About 42,000 hectares of paddy areas were severely affected with an estimated loss of about 30,000 M.T. of rice. As such the rice production has been estimated at 3,75,000 tonnes against 4,05,000 tonnes targeted. To make-up the deficit of production, 17,303 hectares were brought under 1st crop of paddy during 1987-88 and more emphasis is given on Rabi programme for supplementing the deficit the actual area to be irrigated is anticipated at 74,000 hectares.
Government of Manipur, Planning Department